Synthesis of Gold Nanoparticles Capped with Quaterthiophene for Transistor and Resistor Memory Devices - Mai Ha Hoang; Toan Thanh Dao; Nguyen Thi Thu Trang; Phuong Hoai Nam Nguyen; Trinh Tung Ngo (Journal of Chemistry)
Recently, the fabrication of nonvolatile memory devices based on gold nanoparticles has been intensively investigated. In this work, we report on the design and synthesis of new semiconducting quaterthiophene incorporating hexyl thiol group (4TT). Gold nanoparticles capped with 4TT (4TTG) were prepared in a two-phase liquid-liquid system. These nanoparticles have diameters in the range 2–6 nm and are well dispersed in the poly(3-hexylthiophene) (P3HT) host matrix. The intermolecular interaction between 4TT and P3HT could enhance the charge-transport between gold nanoparticles and P3HT. Transfer curve of transistor memory device made of 4TTG/P3HT hybrid film exhibited significant current hysteresis, probably arising from the energy level barrier at 4TTG/P3HT interface. Additionally, the polymer memory resistor structure with an active layer consisting of 4TTG and P3HT displayed a remarkable electrical bistable behavior.